Demystifying Septoplasty in Children - Martins,Mariane Barreto Brandão (2014)
Introduction  Septum deviation in children may alter the early physiologic process of breathing, causing obligatory oral breathing and consequently changing craniofacial development and even intellect. Because of these consequences, septoplasty should be performed as early as possible. Materials and Methods  The retrospective study reviewed the results of septoplasty in 40 children under 12 years old who had follow-up after surgery for a maximum period of 7 years. The research was submitted to the ethics committee and approved with protocol number 10331912.0.0000.0058. Results  Forty patients underwent septoplasty, 39 (97.5%) had cauterization of inferior turbinate and associated procedure, 20 (50%) had adenotonsillectomy, and 17 (42.5%) had adenoidectomy. Conclusion  Nasal septum deviation should be corrected early to provide the harmonious growth of the face and to enable normal development of the child, without the occurrence of nasal deformity.